![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. 1440 : [ 120 - (3x + 9 ) ] = 120
120 - (3x + 9) = 1440 : 120 = 12
3x + 9 = 120 - 12 = 108
3x = 108 - 9 = 99
x = 99 : 3 = 33
b. 120 + [ ( 999 - 9x ) : 60 ] . 24 = 480
[ ( 999 - 9x ) : 60 ] . 24 = 480 - 120 = 360
( 999 - 9x ) : 60 = 360 : 24 = 15
( 999 - 9x ) = 15 . 60 = 900
9x = 999 - 900 = 99
x = 99 : 9 = 11
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x-5)5=(2x-5)3
<=>(2x-5)5-(2x-5)3=0
<=>(2x-5)3[(2x-5)2-1]=0
<=>(2x-5)3(2x-5-1)(2x-5+1)=0
<=>(2x-5)3(2x-6)(2x-4)=0
<=>(2x-5)3=0<=>2x-5=0<=>2x=5<=>x=2,5
hoặc 2x-6=0<=>x=3
hoặc 2x-4=0<=>x=2
Đặt 2x + 5 = t thay vào ta có :
\(t^5=t^3\)
=> t^5 - t3 = 0
=>t^3 ( t^2 - 1 ) = 0
=> t^3 = 0 hoặc t^2 - 1 = 0
=> t =0 hoặc t^2 = 1
=> t = 0 hoặc t = 1 hoặc t = -1
(+) 2x - 5 = 0 => x = 5/2
(+) 2x - 5 = 1 => x = 3
(+) 2x - 5 = -1 => x = 2
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(2x-6\right)^5=\left(2x-6\right)^2\)
\(\Rightarrow\left(2x-6\right)^5-\left(2x-6\right)^2=0\)
\(\Rightarrow\left(2x-6\right)^2\left[\left(2x-6\right)^3-1\right]=0\)
\(\Rightarrow\orbr{\begin{cases}\left(2x-6\right)^2=0\\\left(2x-6\right)^3-1=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}2x-6=0\\\left(2x-6\right)^3=1\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}2x=6\\2x-6=1\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=3\\x=\frac{7}{2}\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2x + 13 = 19
=> 2x = 6
=> x = 3
b) 52x = 530:510
=> 52x = 520 = 52.10
=> x = 10